Infection of Cytomegalovirus in Cholestasis Infant with Biliary Atresia - Lasmauli Situmorang; Bagus Setyoboedi; Sjamsul Arief; Gondo Mastutik (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Biliary Atresia (BA) is extrahepatic cholestasis that results in death within the first two years if the diagnosis and intervention are delayed. The etiology and pathogenesis of BA are still undetermined. Viral infections, including Cytomegalovirus (CMV), are presumed to be one of the causes. Cytomegalovirus infection is more common in intrahepatic than extrahepatic cholestasis such as BA. There are limited data about Cytomegalovirus infection in cholestatic infants with BA. This study compared the incidence of CMV infection in cholestatic infants with biliary atresia and non-biliary atresia. A cross-sectional study was performed in December 2017 - August 2018 in cholestatic infants aged 1-6 months. Liver biopsy, histopathological examination followed by PCR CMV examination were performed on cholestatic infants. The results of the PCR examination were compared between BA and non-BA infants. Statistical analysis of Chi-Square, t-test independent and Mann-Whitney U resulting in p<0.05 were stated as significant. Thirty-seven children were obtained during the study period, consisting of sixteen children with BA and twenty-one children with non-BA. Biliary atresia was predominantly found in female than male children, despite no differences were found between the groups (p=0.163). There were differences in body weight (p=0.002) age (p=0.009), birth weight (p=0.02) and gestational age (p=0.03) between children with BA and non-BA. There was no significant difference in the incidence of CMV infection in cholestatic infants with BA and non-BA (p=0.338). Cytomegalovirus infection in cholestatic infants with BA was less than non-BA cholestatic infants.